2020
DOI: 10.1111/ajgw.12436
|View full text |Cite
|
Sign up to set email alerts
|

Oenococcus oeni, a species born and moulded in wine: a critical review of the stress impacts of wine and the physiological responses

Abstract: Oenococcus oeni is a lactic acid bacterium highly adapted to the stressful environment of wine, and is widely used as an industrial starter culture to conduct malolactic fermentation (MLF), the conversion of L-malate to L-lactate. Some cold-climate wine regions still produce wines which prove too stressful for the application of a starter culture, resulting in sluggish or stuck MLFs which compromise the quality and stability of the wine. The literature on the three primary stress factors, low pH, ethanol and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 158 publications
(326 reference statements)
0
16
0
Order By: Relevance
“…The highest induced and repressed genes, with a log 2 FC of 6.55 and −3.73, correspond to the small heat shock protein Hsp20 and a LysR-type transcriptional regulator (Table S4). Hsp20 (referred to as Hsp18 in several studies) has previously been identified as a response to ethanol and acid stress in O. oeni ( 22 ) and has also been associated with the SO 2 stress response ( 36 ). The involvement of this protein in SO 2 stress is discussed in subsequent sections.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest induced and repressed genes, with a log 2 FC of 6.55 and −3.73, correspond to the small heat shock protein Hsp20 and a LysR-type transcriptional regulator (Table S4). Hsp20 (referred to as Hsp18 in several studies) has previously been identified as a response to ethanol and acid stress in O. oeni ( 22 ) and has also been associated with the SO 2 stress response ( 36 ). The involvement of this protein in SO 2 stress is discussed in subsequent sections.…”
Section: Resultsmentioning
confidence: 99%
“…The toxic mechanisms of SO 2 toward O. oeni are currently unknown; however, modes of action have been suggested, including adduct formation via nucleophilic attack ( 39 ) or, more likely in winemaking environments, oxidative damage through autoxidation of SO 2 and generation of sulfuroxy radicals ( 22 ). Under oxidative stress caused by radicals, proteins containing cysteine and methionine residues are prone to oxidation at their electron-rich sulfur atoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations